Authigenetic K-feldspars and their relations to Sn polymetallic mineralization in the Dachang ore field - Pan, Jiahua; Amstutz, Christian (Chinese journal of geochemistry, 1993)
Sn-polymetallic ores at Dachang, Guangxi Autonomous Region, China, are hosted in Middle-Upper Devonian reef limestones, siliceous rocks, banded and lenticular limestones, etc. Two types of orebodies can be distinguished according to their relations to the bedding: one is distributed along the bedding and the other cuts across the bedding. Sn and sulfide orebodies associated with K-feldspars are mostly characterized by laminated ore structure.
Gesehen am 15.02.2023